Digital Business Development - Möglichkeiten und Grenzen neuer Geschäftsmodelle - Hubert Vogl; Philippe Tufinkgi; Moritz Venschott (IUBH Internationale Hochschule, 2020)
– Digitization not only makes it possible to expand existing business models with digital service functions, digitization also enables completely new business models. The digital technologies can be existential for a business model or support you in achieving a new cost / benefit ratio through an increased value proposition. For example, sales and communication channels, sources of income or complete products and services can be rethought or newly combined. Digital Business Development supports organizations in developing digital business models and successfully implementing them in operational practice. The following discussion paper deals with the possibilities and limits of new business models. The focus here is on selected patterns of digital business models and their far-reaching changes in industry, trade and services. The discussion focuses on the following question: What opportunities do new business models offer and what are their challenges and limits? First, the basics of business development in the digital age are outlined. The potential and challenges of selected patterns of digital business models are then presented. It concludes with a critical reflection on the limits of digital business models based on the knowledge gained. The importance of the factors "people and the real economy" in the digital age is emphasized.
Keywords: 650; Digitale Geschäftsmodelle; Business Development; Ambidexteritätsproblematik; Value Proposition